Biofilm grown on wood waste pretreated with cold low-pressure nitrogen plasma: Utilization for toluene remediation. (April 2019) - Farber, Ravit; Dabush-Busheri, Inbal; Chaniel, Gilad; Rozenfeld, Shmuel; Bormashenko, Edward; Multanen, Victor; Cahan, Rivka
Abstract: Wood waste was pretreated with cold low-pressure nitrogen plasma (LPN-plasma), in an attempt to increase the bacterial attachment and biofilm viability. Biofilm viability was examined in the presence of exogenously added P. putida as well as B. cereus . Pretreatment of wood waste to LPN-plasma led to a 3.5-fold increase in biofilm viability of the exogenously added P. putida F1 in MMT (minimal medium supplied with toluene) and a 1.6-fold increase in MMG (minimal medium supplied with glucose), compared to the untreated wood waste. The increase in biofilm viability was also observed with the exogenously added B. cereus. The LPN-plasma-treated wood waste as well as the bacterial cell surface exhibited a highly hydrophilic pattern. SEM analysis of the LPN-plasma-treated wood waste showed a significant change in the internal surface topography. Biofilms of P. putida and B. cereus grown on wood waste pretreated with LPN-plasma led to 91% and 89% toluene degradation, respectively, whereas biofilms grown on untreated wood waste led to toluene degradation of 78% and 58%, respectively. To the best of our knowledge, this is the first study to describe the effect of plasma-pretreated wood waste on biofilm formation and implementation of this technology in contaminated soil bioremediation process. Highlights: Hydrophilic pattern of the wood surface was obtained upon cold plasma treatment. Treatment of wood waste using plasma caused a change in its surface topography. Enhancement of biofilm viability was due to treatment of wood waste with plasma. Biofilm grown on plasma-treated wood waste led to a higher toluene degradation.